Age-related adaptation features of teachers of educational institutions - Arystanbay, A.A.; Smagulov, N.K.; Tykezhanova, G.M.; Svetlik, M.V. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
Modern educational reforms require teachers to be highly qualified and to adapt quickly to new working methods, including the use of digital technologies. The problem of teachers’ professional adaptation remains relevant despite a large number of studies in this field. Aim: to determine the factors influencing the professional adaptation of teachers in educational institutions, as well as to analyze the age characteristics of adaptation and the psychophysiological characteristics of teachers. The study involved 137 teachers from the city of Karaganda, who were divided into three age groups: under 30 years, 30–45 years and over 45 years. The Spielberger–Khanin test was used to assess anxiety, the WAM test was applied for subjective assessment of well-being, activity and mood, the Anfimov’s correction tables were used to study mental performance, as well as physiological methods (blood pressure measurement, analysis of heart rate variability). The level of reactive anxiety among teachers did not show significant differences between the groups. However, the analysis of well-being, activity, and mood showed that well-being decreased with age, activity levels showed slight fluctuations, and mood was higher in the first group. Mental performance also decreased with age, which was confirmed by the decrease in the number of viewed and found signs. In addition, an increase in blood pressure, heart rate, and the stress index of regulatory systems was observed. Higher activity of the sympathetic nervous system and pronounced functional tension of regulatory systems were also identified in the older groups. The results of the study confirm the need to support teachers at different stages of their professional activities. Measures aimed at reducing stress load and increasing teachers’ level of adaptation in the context of the digital transformation of education are particularly important.
Жалпы білім беру мекемелері мұғалімдерінің бейімделуінің жас ерекшеліктері
Возрастные особенности адаптации учителей общеобразовательных учреждений
Keywords: teachers of educational institutions; age dynamics; adaptation; psychophysiological state; working capacity